Using a simple model to systematically examine the influence of force-velocity profile and power on vertical jump performance with different constraints - Haug, W. B.; Pain, M. T. G. (Sports Biomechanics, 2024)
Power, and recently force-velocity (F-V) profiling, are well-researched and oft cited critical components for sports performance but both are still debated; some would say misused. A neat, applied formulation of power and linear F-V in the literature is practically useful but there is a dearth of fundamental explanations of how power and F-V interact with human and environmental constraints. To systematically explore the interactions of a linear F-V profile, peak power, gravity, mass, range of motion (ROM), and initial activation conditions, a forward dynamics point mass model of vertical jumping was parameterised from an athlete. With no constraints and for a given peak power, F-V favouring higher velocity performed better, but were impacted more under real-world conditions of gravity and finite ROM meaning the better F-V was dependent on constraints. Increasing peak power invariably increased jump height but improvement was dependent on the initial F-V and if it was altered by changing maximal force or velocity. When mass was changed along with power and F-V there was a non-linear interaction and jump improvement could be almost as large for a F-V change as an increase in power. An ideal F-V profile cannot be identified without knowledge of mass and ROM.